LOS JUEGOS COMO RECURSO DIDACTICO PARA EL DESARROLLO PSICOMOTOR DE LOS NIÑOS DE 5 A 10 AÑOS DE LA UNIDAD EDUCATIVA 24 DE MARZO DEL CANTÓN COCA, PROVINCIA DE ORELLANA - Varas Carranza, Lister Fernando (2024)
Games are a valuable tool to foster the development of psychomotor skills in children. Through games, infants can improve their coordination, balance, laterality, fine and gross motor skills. The objective of this degree work is to analyze which games can be used as a didactic resource that favors the psychomotor development of children from 5 to 10 years old in the 24 de marzo Educational Unit in the Coca canton, province of Orellana. The sample consisted of 30 children in the 6th grade of the school, and the Movement Assessment Battery for Children-2 (MABC-2), within the results, a solid theoretical and practical support is offered for the implementation of the game as a didactic resource from postural control, muscle tone and balance, with the objective of promoting the psychomotor development of children from 5 to 10 years old. The findings obtained and the strategies proposed are very useful for teachers and the educational community, in order to optimize the teaching-learning processes and contribute to the integral development of the students.